Pemberian Naphthalene Acetic Acid (NAA) dan Kinetin Terhadap Multiplikasi Tunas Tanaman Jahe (Globba leucantha var. bicolor Holttum) pada Kultur In Vitro - Mawaddah, Syerin Kusuma; Saputro, Nurcahyo Widyodaru; Lestari, Ani (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Globba leucantha var. bicolor Holttum is a part of Zingiberaceae plant that is not yet widely known but can be used as a medicinal material as well as an ornamental plant. So far Globba plant propagation has not been widely done and has relied solely on from its habitat. Research aims at acquiring Naphthalene Acetic Acid (NAA) concentrations and optimal kinetin for the multiplication of ginger plant shoots (Globba leucantha var. bicolor Holttum) on in vitro culture. The research method uses experimental methods with non-parametric statistics and 24 repeated treatments 3 times as well as being analyzed descriptively using the Kruskal Wallis Test. The treatment used NAA with concentrations of 0 mg/l, 0.1 mg/l, 0.5 mg/l, 1 mg/l, 1.5 mg/l, and 2 mg/l combined with Kinetin with concentrations of 0 mg/l, 0.1 mg/l, 1 mg/l and 10 mg/l. The results showed that the growth of Globba plant's best shoots at N3K3 treatment (NAA 1 mg/l + Kinetin 10 mg/l) with a shoot emergent time of 21.58 HSI, a percentage of shoot forming 66.67%, a shot count of 0.89 buds per explant, and a shoot length of 0.18 cm. Additionally at the same time also formed Globba plant roots with the best treatment of N5K2 (NAA 1 mg/l + Kinetin 10 mg/l) with a time of appearing rooted 25.67 HSI and a root count of 7.78 roots per explant.